Cosmos Verses in Agus Purwanto's Review - M Muqtadir (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
Agus Purwanto interpretation of the cosmos in a broad outline is science around the universe as a whole. The universe is so rich in planets orbiting stars, gathered in galaxies. Agus Purwanto interpretation the cosmos is divided into two implications. 1) the implication of contemporary interpretation development, which is marked by the integration of the worlds of interpretations around the cosmos, one of which is in interpretation by using the theoretical scholars and early cosmologists and the counts with the precision of the verse, thus producing an interpretation that matches the observation of sophisticated instruments. 2) the implications for science, one marked in its integration on the development of western science that is spreading in understanding contrary to any religious teaching. Agus Purwanto moves to deflect the understanding with its interpretation of verses of the cosmos.